Non-Native German Secondary School Teachers’ Beliefs And Practices In The Integration Of Culture In Teaching German As A Foreign Language In Malaysia - Kok, Foong Moi (2023)
This mixed-methods study surveyed 66 teachers and interviewed five participants to explore the beliefs of non-native German teachers in Malaysian secondary schools and how these beliefs influence their practices in integrating cultural elements into GFL instruction. The study found that the majority of teachers held positive beliefs about incorporating cultural elements in GFL classes and recognised the need to create a cultural learning environment.